2020
DOI: 10.3390/agronomy10121923
|View full text |Cite
|
Sign up to set email alerts
|

Adult Desert Locust Swarms, Schistocerca gregaria, Preferentially Roost in the Tallest Plants at Any Given Site in the Sahara Desert

Abstract: The desert locust, Schistocerca gregaria, is a major migratory pest that causes substantial agricultural damage. Flying adult swarms disperse widely during the daytime, but they densely roost on plants at night. Swarm control operations are generally conducted during the daytime, but night-time control is a significant potential alternative. However, the night-roosting behavior of swarms is poorly understood. We determined night-roosting plant preferences of migrating sexually immature swarms of S. gregaria at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…A field study conducted in Mauritania [77] confirmed observations that marching nymphal desert locust bands passed some plants and eventually roosted on patchily distributed trees near dusk, forming aggregations [79]. Maeno and Babah [77] found that gregarious bands of nymphs condensed on, and around, the largest tree in the local plant community; adults mostly roosted on large trees and substantial bushes [80,81]. Surveillance might also benefit from findings that indicate variability desert locust defensive responses to predators and likely to approaching terrestrial surveillance personnel (on foot and in vehicles).…”
Section: Outbreak Prevention: Salient Requirementsmentioning
confidence: 73%
“…A field study conducted in Mauritania [77] confirmed observations that marching nymphal desert locust bands passed some plants and eventually roosted on patchily distributed trees near dusk, forming aggregations [79]. Maeno and Babah [77] found that gregarious bands of nymphs condensed on, and around, the largest tree in the local plant community; adults mostly roosted on large trees and substantial bushes [80,81]. Surveillance might also benefit from findings that indicate variability desert locust defensive responses to predators and likely to approaching terrestrial surveillance personnel (on foot and in vehicles).…”
Section: Outbreak Prevention: Salient Requirementsmentioning
confidence: 73%
“…Desert locust behaviour and dispersal patterns are complex processes that depend on environmental factors such as temperature [36], precipitation [22,37], the condition of vegetation [38][39][40], soil moisture [41,42], soil composition [41] and the wind [36]. These factors can create either stimulatory or inhibitory conditions for gregarisation, desert locust migration and breeding.…”
Section: Discussionmentioning
confidence: 99%
“…First, concerning the behavioral aspects, Maeno et al [70] studied the previously poorly understood nocturnal behavior of swarms of the Desert Locust, Schistocerca gregaria. This nocturnal behavior appears to be predictable and dependent on plant size, and the authors propose that it can be used to facilitate locust swarm management and to adopt a general strategy of nocturnal locust control.…”
Section: Summary Of Articles Included In This Special Issuementioning
confidence: 99%